The Effect of The Drill Training Method on Increasing the Accuracy of Volleyball Services - Kharisma, Yudhi; Mubarok, Moch. Zakky; Hermawan, Bagus (Physical Activity Journal (PAJU), 2024)
This study aimed to examine the method to improve the accuracy of the upper serve in volleyball games. The method applied is experimental with a pretest-posttest design. The research participants are 20 female active students of SMPN 1 Tukdana who attend volleyball extracurricular activities. The treatment provided is top-service training using the drill method with target aids. The instrument utilized was the volleyball skills test from Russell-Lange. This skills test measures the level of service mastery in volleyball. The research results obtained an average initial test of 14.75, a final test of 25, a standard deviation of the initial test of 3.08, and a final test of 4.59. Data analysis results of normality test L count < L table is 0.04. This number stated the normal result because its value is lower than the maximum passing grade (< 0.20). Due to the results of the calculations, t count < t table, specifically 1.73, is < 2.10, which means that Ho is accepted. The results reveal that applying the drill training method effectively improves the quality of the volleyball top serve.